2020
DOI: 10.1098/rsob.190235
|View full text |Cite
|
Sign up to set email alerts
|

Neoleukin-2 enhances anti-tumour immunity downstream of peptide vaccination targeted by an anti-MHC class II VHH

Abstract: Cancer-specific mutations can lead to peptides of unique sequence presented on MHC class I to CD8 T cells. These neoantigens can be potent tumour-rejection antigens, appear to be the driving force behind responsiveness to anti-CTLA-4 and anti-PD1/L1-based therapies and have been used to develop personalized vaccines. The platform for delivering neoantigen-based vaccines has varied, and further optimization of both platform and adjuvant will be necessary to achieve scalable vaccine products that are therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Not only do our data correspond with a T cell-mediated mechanism of tumour control, but they also generally corroborate data indicating that combining radiation with anti-PD-L1 or with checkpoint blockade and anti-CD40 therapy slows tumour growth in a KPC model of pancreatic cancer [ 43 , 44 , 50 ]. Other attempts at T cell priming using peptide-based vaccines or other T cell-directed therapies that do not induce tumour cell death have been less effective, suggesting that release of tumour antigens from dying malignant cells is a critical component of successful immunotherapy in PDAC [ 23 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only do our data correspond with a T cell-mediated mechanism of tumour control, but they also generally corroborate data indicating that combining radiation with anti-PD-L1 or with checkpoint blockade and anti-CD40 therapy slows tumour growth in a KPC model of pancreatic cancer [ 43 , 44 , 50 ]. Other attempts at T cell priming using peptide-based vaccines or other T cell-directed therapies that do not induce tumour cell death have been less effective, suggesting that release of tumour antigens from dying malignant cells is a critical component of successful immunotherapy in PDAC [ 23 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-CD11b nanobody produced the most significant activation of CD8 + T cells [ 103 ]. Crowley et al also created nanobody-conjugated peptide vaccines that targeted MHC-II for APC delivery and showed improved vaccine-mediated CD8 + T cell activation [ 104 ]. In addition, many nanobodies target APCs whose antigens have yet to be discovered, such as DC1.8, DC2.1, and R3_13 nanobodies [ 105 , 106 ].…”
Section: Targets and Applications Of Nanobodiesmentioning
confidence: 99%
“…Nanobody-LVs have shown specific DC transduction ( 135 ) in vitro , but a subsequent study suggested that broad tropism LVs may be more effective in inducing an anti-tumor response ( 136 ). Furthermore, Crowley et al ( 137 ) developed nanobody-conjugated peptide vaccines targeting MHC-II for APC delivery, demonstrating enhanced vaccine-mediated CD8 + T cell activation in vivo .…”
Section: Nanobodies: Synergy With Other Cancer Therapeuticsmentioning
confidence: 99%